Hydrocarbons Biodegradation by Rhodococcus: Assimilation of Hexadecane in Different Aggregate States - Luong Thi Mo; Puntus Irina; Suzina Natalia; Nechaeva Irina; Akhmetov Lenar; Filonov Andrey; Akatova Ekaterina; Alferov Sergey; Ponamoreva Olga (Microorganisms, 2022)
The aim of our study was to reveal the peculiarities of the adaptation of rhodococci to hydrophobic hydrocarbon degradation at low temperatures when the substrate was in solid states. The ability of actinobacteria Rhodococcus erythropolis (strains X5 and S67) to degrade hexadecane at 10 °C (solid hydrophobic substrate) and 26 °C (liquid hydrophobic substrate) is described. Despite the solid state of the hydrophobic substrate at 10 °C, bacteria demonstrate a high level of its degradation (30–40%) within 18 days. For the first time, we show that specialized cellular structures are formed during the degradation of solid hexadecane by Rhodococcus at low temperatures: intracellular multimembrane structures and surface vesicles connected to the cell by fibers. The formation of specialized cellular structures when Rhodococcus bacteria are grown on solid hexadecane is an important adaptive trait, thereby contributing to the enlargement of a contact area between membrane-bound enzymes and a hydrophobic substrate.